Human hair and the impact of cosmetic procedures: a review on cleansing and shape-modulating cosmetics - Cruz, Célia F. (2016)
Hair can be strategically divided into two distinct parts: the hair follicle, deeply buried in the skin, and the visible hair fiber. The study of the hair follicle is mainly addressed by biological sciences while the hair fiber is mainly studied from a physicochemical perspective by cosmetic sciences. This paper reviews the key topics in hair follicle biology and hair fiber biochemistry, in particular the ones associated with the genetically determined cosmetic attributes: hair texture and shape. The traditional and widespread hair care procedures that transiently or permanently affect these hair fiber features are then described in detail. When hair is often exposed to some particularly aggressive cosmetic treatments, hair fibers become damaged. The future of hair cosmetics, which are continuously evolving based on ongoing research, will be the development of more efficient and safer procedures according to consumers needs and concerns.